Biochemical Characterization of New Sweet Orange Mutants Rich in Lycopene and β-Carotene Antioxidants - Lourdes Carmona; Berta Alquézar; Leandro Peña (MDPI AG, 2024)
Carotenoid-rich foods such as citrus fruits have a wide range of functions in human health. They primarily exert antioxidant effects, but individual carotenoids may also act through other health-promoting mechanisms such as β-carotene as pro-vitamin A. Here, we show that red-fleshed sweet oranges grown in tropical climates are 4-9 times richer in carotenoids than their orange-fleshed counterparts, regardless of their maturation stage. The most significant difference observed between both varieties was the presence of lycopene at moderate concentrations (around 8 µg/g FW) in the mature pulp of the red varieties, which was absent in the blond ones. This is because the red-fleshed sweet oranges grown in tropical climates with high temperatures increase lycopene and β-carotene concentrations in their pulp during fruit maturation. Due to lycopene accumulation, red orange juice offers a promising addition to popular blond-orange, with the new varieties Carrancas and Pinhal being perfectly suitable for blending to enhance juice colour. Sao Paulo, one of the world's leading citrus orange juice producers, as well as other tropical citrus regions could benefit from cultivating using such lycopene-rich cultivars and industrially.